Epidemiological aspects of mansonic schistosomiasis in the neighbors Novo Horizonte and Campo Limpo, Feira de Santana, state of Bahia - Oliveira, Alany Santos; Santos, João Francisco (SITIENTIBUS série Ciências Biológicas, 2002)
Most people from the city of Feira de Santana, Bahi State, suffer from diseases caused by intestinal parasites. These diseases, which are influenciated by poor sanitary conditions, low education and hygiene, becomes a serious problem of health public. An epidemiological study on schistosomosis mansoni was carried out in the suburbs of Novo Horizonte and Campo Limpo. Fecal examinations were done at the Parasitological Laboratory of the Univesidade Estadual de Feira de Santana (UEFS) during the years 1998 and 2001. By using spontaneous sedimentation method, 3.514 samples were studied from Novo Horizonte and 4.652 from Campo Limpo, which presented positive rate of 4.61% and 2.06% respectively. Considering the genera, both male and female have showed similar positive rates. The results demonstrate that a collaborative action between the public health organizations is necessary in order to achieve a suitable solution for the problem.